3D-printed polymeric lattice-enhanced sustainable municipal solid waste incineration fly ash alkali-activated cementitious composites. (December 2022) - Dong, Peng; Ding, Weijian; Yuan, Hongyan; Wang, Quan
Abstract: The disposal of municipal solid waste incineration fly ash (MSWIFA) has become a prominent issue due to high environmental risks. In this study, as a potential aluminosilicate precursor, MSWIFA was further alkali-activated as a sustainable construction material in the form of an alkali-activated MSWIFA-based material (AAFM), with a low leaching level of heavy metals. Various 3D-printed polymeric lattices were designed and inserted into the AAFM to promote its inherent brittleness. A special coating was also considered to enhance the alkali resistance of the PEGT lattices. Through a flexural tension test with a 3D digital image correlation (3D-DIC) technique, the failure patterns and strain distributions of the 3D-printed polymeric lattice-enhanced MSWIFA-based composites were tracked. These polymeric lattice-containing composites indicated the promotion of mechanical performance, i.e., higher flexural strengths and good ductility. The 3D polymeric lattice-enhanced MSWIFA-based composites showed application prospects as sustainable construction materials, gaining both environmental benefits and good mechanical performance. Highlights: Municipal solid waste incineration fly ash was alkali-activated as a sustainable construction material. 3D-printed polymeric lattices with intelligent structures were designed and manufactured. 3D-printed polymeric lattice-enhanced cementitious composites were fabricated. The 3D-printed polymeric lattice-enhanced cementitious composites showed greatly improved ductility and flexural strength.